EP388/#630 Creating a multidisciplinary protocol for the administration of hyperthermic intraperitoneal chemotherapy with cisplatin: a single-institution experience. (4th December 2022) - Praiss, Aaron; Moukarzel, Lea; Dessources, Kimberly; Sonoda, Yukio; Roche, Kara Long; Gardner, Ginger; Tew, William; Grisham, Rachel; Chi, Dennis; O'Cearbhaill, Roisin; Zivanovic, Oliver
Abstract : Objectives: Hyperthermic intraperitoneal chemotherapy (HIPEC) with cisplatin at time of interval cytoreductive surgery (iCS) has shown to improve oncologic outcomes in patients with advanced-stage epithelial ovarian cancer (EOC). We report initial outcomes of a multidisciplinary protocol for perioperative management of patients receiving HIPEC. Methods: An institutional protocol was created with medical oncology, surgical, anesthesia, nursing, and pharmacy teams. From 1/1/2020 – 5/1/2022, patients with pathology-confirmed, radiologic stage III EOC and an Eastern Cooperative Oncology Group (ECOG) performance status between 0–1 were deemed eligible for HIPEC at time of iCS. Patient demographics, clinicopathologic characteristics, and perioperative outcomes were prospectively collected. Descriptive analyses were performed. Results: Twenty consecutive patients were scheduled for HIPEC at iCS. The median age was 64 years (range, 39–76). Four patients did not receive HIPEC due to preoperative thrombocytopenia, cardiac comorbidities, hearing loss, or intraoperative decision to abort iCS secondary to extent of disease. Ten patients (63%) completed 3 cycles of neoadjuvant chemotherapy. Complete gross resection (CGR) was achieved in 69% (n=11) of cases. Bowel resections were performed in 10 patients (63%), and all anastomoses were performed prior to HIPEC administration without diverting ostomies. Two patients (12.5%) experienced serious adverse events: an abdominal infection requiring reoperation and an acute kidney injury requiring hemodialysis. There were no perioperative deaths. The median time to start postoperative chemotherapy was 33 days (range, 20–71). Conclusions: The risk of HIPEC is acceptable when administered using a standard protocol and multidisciplinary team approach. Renal protection protocols are necessary to decrease risk of nephrotoxicity and improve perioperative outcomes.